POLA RUANG KOMUNAL DI RUMAH SUSUN BANDARHARJO SEMARANG - PURWANTO, Edi (Dimensi: Journal of Architecture and Built Environment, 2012)
Behind the good will of government to build flats for low-income communities, there was a reduction of socio-cultural essence of life of its inhabitants. Reduction is happening in social interaction, initially living in a neighboring village, later turned into a mood of alienation and limitations because living in flats story a lot. This study used qualitative rationalistic approach, which aims to reveal the patterns of communal space as a space of social interaction of residents, expected results will be the next design evaluation flats. Research on patterns of communal space is taking the case of flats located in the Bandarharjo. More than eighteen years, residents tried to build social interaction with neighbors although no longer made in the halls of the road as well as in the villages. Their efforts are utilizing the functions of each floor of the building and the lobby open spaces around the ground floor of the building for social interaction among residents. Utilization of space functions has resulted in a communal space patterns in groups with the intensity of the use of high, medium, and low. The communal lounge with high intensity use tend to be close to their house.